Survey on PJOK Facilities and Infrastructure In Online Learning In The Era of Covid-19 at The State Elementary School on Gondang District, Sragen Regency - Fajar Aria Abidin; Agus Mukholid; Deddy Whinata Kardiyanto (Universitas Sebelas Maret, 2021)
The purpose of this study was to determine the state of PJOK facilities and infrastructure in online learning in the covid-19 era in State Elementary Schools throughout Gondang District, Sragen Regency in 2020/2021. This research is descriptive qualitative. The population in this study were all State Elementary Schools in Gondang Sub-district, Sragen Regency in 2020. Data collection in this research study on the state of Physical Education and Health (PJOK) facilities and infrastructure for Public Elementary Schools in Gondang District, Sragen Regency included observations, interview guidelines. and observation. The data analysis technique used a descriptive percentage formula which was carried out by dividing the total score obtained by the ideal score and multiplied by 100%. The research procedure includes the research stage, the proposal preparation stage, the instrument preparation stage, the data collection stage, the data analysis stage, and the reporting stage. The results of data analysis can be conveyed as follows: (1) facilities and infrastructure that are suitable for use and included in the very good category are Whatsapp Group, the use of Youtube and Google Classroom links including facilities that are suitable for use but need changes, while facilities and infrastructure that are not worth using and included in the very bad category are Zoom Apps; (2) the overall interaction in PJOK online learning has been effective; (3) there are obstacles that occur during the implementation of online learning, namely, less effective learning, limited facilities and infrastructure, difficulty for students to understand the explanation from the teacher, signal constraints, lack of enthusiasm for students, constrained tools used to communicate, and lack of parental supervision; (4) future expectations for the implementation of PJOK online learning, namely that face-to-face learning will soon be re-implemented, online learning is carried out by visiting students' homes with small groups (3-5 children), the online learning implementation system is further improved, with the implementation of online learning It is hoped that there will be a curriculum renewal that is in accordance with current conditions, facilities and infrastructure need to be improved, parental care is needed, the cohesiveness of educators needs to be improved, online learning is carried out with constant monitoring, and students are expected to be more active.